Immune response of S. Typhi-derived Vi polysaccharide and outer membrane protein a conjugate in mice - Shabirul Haque; Sanjukta Sengupta; Azhar Khan; Asok Kumar Mukhopadhyay; Maharaj Kishan Bhan; Ramesh Kumar; Bansilal Jailkhani (Elsevier, 2023)
Typhoid fever is a serious concern precisely in developing nations. Still investigators are exploring a better conjugate partner for Vi-polysaccharide to develop a more effective vaccine for typhoid fever. Here, we cloned and expressed S. Typhi outer membrane protein A (OmpA). The conjugation of Vi-polysaccharide with OmpA was carried out by the carbodiimide (EDAC) method employing ADH as a linker. Total Ig and IgG generated against OmpA, and Vi polysaccharide was quantified by ELISA. Vi polysaccharide alone induced very low levels of Vi polysaccharide antibody. Vi-OmpA conjugate (Vi-conjugate) elicited a robust immune response compared to Vi polysaccharide alone and showed booster response. Further, IgG was only evoked by Vi-OmpA conjugate, not with Vi polysaccharide alone. OmpA antibody induction in both the Vi-OmpA conjugate and OmpA were similar level. Taken together, we show that OmpA as a carrier protein conjugated to Vi polysaccharide is immunogenic. We predict OmpA antibodies will contribute protection along with antibodies generated by Vi-polysaccharide. Past and current literature supports that OmpA is highly conserved protein not only among Salmonellae but entire Enterobacteriacea family with 96-100% identity.